Memories of a special Csm (Rivista di Studi e Ricerche sulla criminalità organizzata, 2022)
The article is a testimony on the positions held by Carlo Smuraglia in one of the most famous conflicts that have marked the history of Italian justice: the one to promote or marginalize Giovanni Falcone within the Sicilian judiciary in the highest phase of the fight against the mafia. This is the memory of a magistrate who was a participating and passionate observer of that story. He conveys an image of coherence and linearity of the institutional commitment of the Milanese professor-lawyer.
Keywords: Carlo Smuraglia, Giovanni Falcone, Mafia, Magistrates’ governing council, Paolo Borsellino